2022
DOI: 10.1001/jamanetworkopen.2022.21608
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Maternal Milk Feeding With Neurodevelopmental Outcomes at 7 Years of Age in Former Preterm Infants

Abstract: Key Points Question What are the associations between maternal milk feeding and cognitive, academic, and behavioral outcomes of preterm infants born at less than 33 weeks’ gestation? Findings In this cohort study of 586 preterm infants, higher maternal milk intake during neonatal hospitalization was associated with higher performance IQ, better academic achievement in reading and math, and fewer attention-deficit/hyperactivity symptoms at 7 years of age. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 56 publications
0
21
0
Order By: Relevance
“…Preterm infants are more susceptible to neurodevelopmental deficits into childhood, which result from brain injuries occurring around the time of birth as well as impaired brain maturation while in the neonatal intensive care unit (NICU). Preterm infants who are fed human milk, however, have improved neurodevelopmental outcomes in the NICU, particularly preterm infants born <30 weeks of gestation [ 43 ]. Moreover, quantitative MRI studies of the preterm brain demonstrate that human milk feeding is associated with more mature cerebral white matter, less injury, and larger regional volumes, providing potential pathways to better neurodevelopmental outcomes in this population [ 10 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Preterm infants are more susceptible to neurodevelopmental deficits into childhood, which result from brain injuries occurring around the time of birth as well as impaired brain maturation while in the neonatal intensive care unit (NICU). Preterm infants who are fed human milk, however, have improved neurodevelopmental outcomes in the NICU, particularly preterm infants born <30 weeks of gestation [ 43 ]. Moreover, quantitative MRI studies of the preterm brain demonstrate that human milk feeding is associated with more mature cerebral white matter, less injury, and larger regional volumes, providing potential pathways to better neurodevelopmental outcomes in this population [ 10 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to a dearth of economic data for mothers of PT infants specifically, we reviewed US national data on overall maternal labor force participation, employment, and earnings by race and ethnicity. Although other factors such as antenatal steroids and coordinated evidence-based “Golden Hour” care administered in the first 60 min of life also impact health outcomes for PT infants [ 53 , 54 ], this review examines the role of MOM provision as a modifiable factor for improving PT infant health and how work as a social determinant of health may explain differences in MOM provision by maternal race and ethnicity [ 13 , 55 , 56 , 57 ].…”
Section: Introductionmentioning
confidence: 99%
“…Breastfeeding is considered as an optimal way to feed infants during the neonatal period, providing them with the developmental nutrients needed and shaping their immune systems ( 1 ). Most studies have shown that exclusive breastfeeding provides potential long-term benefits to neurodevelopment ( 2 , 3 ). Interrupting breastfeeding to treat breast milk jaundice (BMJ) has long been controversial and may increase the risk of early termination of breastfeeding ( 4 ).…”
Section: Introductionmentioning
confidence: 99%